Changes in endothelial progenitor cell subsets in normal pregnancy compared with preeclampsia. Issue 6 (June 2015) - Parsanezhad, Mohammad‐Ebrahim; Attar, Armin; Namavar‐Jahromi, Bahia; Khoshkhou, Sara; Khosravi‐Maharlooei, Mohsen; Monabati, Ahmad; Habibagahi, Mojtaba
Abstract : Background : The results of studies measuring the number of endothelial progenitor cells (EPCs) in normal pregnancies and in preeclampsia have been highly controversial or even contradictory because of cross‐sectional designs and different methodologies enumerating three distinct subsets of EPCs: circulating angiogenic cells (CAC), colony‐forming unit endothelial cell (CFU‐ECs), and endothelial colony forming cells (ECFCs). To provide a clear explanation for these underlying controversies, we designed a prospective study to compare the number of all EPC subsets between three trimesters of normal gestation and a case–control study to compare these values as preeclampsia occurs with those from gestational age (GA) matched normal pregnancy. Methods : Samples from peripheral blood of nine women were taken during their three consecutive trimesters of normal pregnancy, and from eight women with preeclampsia. To cover most of the reported phenotypes for CACs and ECFCs in the literature, we enumerated 13 cell populations by quantitative flow cytometry using various combinations of the markers CD34, CD133, CD309, and CD45. We used routine culturing techniques to enumerate CFU‐ECs. Results : The numbers of CACs and ECFCs were higher in women with preeclampsia ( p = 0.014). By contrast, preeclampsia was associated with a reduced number of CFU‐ECs ( p = 0.039). The CAC number rose with the increase in GA ( p = 0.016) during normal pregnancy, while the number of CFU‐ECs and ECFCs did not differ during the trimesters. Conclusion : Although we did demonstrate an increase in absolute counts of CACs and ECFCs in preeclampsia, fewer colony formation capacities indicated a loss in their functional capabilities. By contrast, the number of CACs increased without alterations in colony formation ability in normal pregnancy with the growth of the fetus. Here, by comparing different methodologies to calculate the number of EPC subsets, we could imitate the existing controversy in the literature for such calculations, which may help to elucidate clearer explanations.